Optimization of the combustion chamber geometry and injection parameters on a light-duty diesel engine for emission minimization using multi-objective genetic algorithm - GÜL, MEHMET ZAFER (ELSEVIER SCI LTD, 2021)
Combustion efficiency and exhaust emission of the compression-ignition engines are highly dependent on the combustion chamber design. In this study, shape optimization was performed to reduce the emissions and maximize the combustion efficiency of a compression ignition engine with the guidance of computational fluid dynamics (CFD). The aim was to optimize diesel combustion efficiency while maintaining engine power and torque. A double-swirl piston bowl is used, and the bowl depth, bowl diameter, and other dimensions of the piston bowl are optimized to minimize the soot and NOX emission while meeting the IMEP target. The spray angle of the injector, SOI, and injector protrusion were parametrized to meet the optimization targets. The numerical model was developed using Converge software. CAESES software and multi-objective genetic algorithm (MOGA) were used to automatically change the chamber design parameters and to optimize the piston bowl geometry. A total of 104 different combustion chamber designs and 23 varied injection parameters were determined parametrically and the optimum case was decided with the MOGA. A comprehensive optimization study was carried out using experimental, CFD, and MOGA methods. Compared to the baseline design, the optimized new piston bowl design has provided enhanced in-cylinder air utilization and rapid mixing-controlled combustion, resulting in enhanced fuel efficiency. The optimized design emits remarkably lower NOX and soot emissions.
Keywords: Optimization; CI engine; CFD; Emission; Combustion; SYSTEM